(untitled) (MMIT Proceedings, 2025)
This article describes the need for pedagogical and psychological research in the formation of ideological immunity in the education of young people in the context of globalization, as well as the analysis of the direction of research in this direction. The article mentions the need to introduce programs into the education system aimed at protecting the minds of young people from foreign ideas and inculcating them with healthy religious views in today’s era of globalization.